Resistance to the influences of others: Limits to the formation of a collective memory through conversational remembering - Muller, Felipe Juan (2010)
People often form collective memories by sharing their memories with others. Warnings about the reliability of one conversational participant can limit the extent to which conversations or other forms of postevent information can influence subsequent memory. Although this attenuation is consistently found for prewarnings, there are substantial reasons to suspect that, by carefully manipulating both individual characteristics of the listener in a conversation and the dynamics of the postevent conversation, one can restrict the effect even prewarnings have on the influence a speaker might have on the memory of a listener. Indeed, in situations in which a speaker contributes substantially to a conversation and the quality of memory of a listener is poor, prewarnings have the paradoxical effect of increasing the influence of the speaker on a listener's memory. Warnings may not always limit the formation of a collective memory.